The answer is D. m≥0.
First the inequality must be simplified.
5(-4m-4)-8(3m+7)≤-76
5*-4m=-20m
5*-4=-20
-8*3m=-24m
-8*7=-56
-20m-20-24m-56≤-76
Now the like terms must be combined.
-20m+-24m=-44m
-20+-56=-76
-44m-76≤-76
Add positive 76 to both sides of the inequality.
-44m-76+76≤-76+76
-44m≤0
Divide both sides by -44.
≤
![(0)/(-44)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/6554594rsjfod3chm92ktprgb35qv844ic.png)
m≥0
(When dividing with a negative number in inequalities, the sign has to be flipped.)